Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41598-020-76633-x
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and transcriptional analyses provides new insights into the molecular mechanisms underlying root thickening and isoflavonoid biosynthesis in Callerya speciosa (Champ. ex Benth.) Schot

Abstract: Callerya speciosa (Champ. ex Benth.) Schot is a traditional Chinese medicine characterized by tuberous roots as the main organ of isoflavonoid accumulation. Root thickening and isoflavonoid accumulation are two major factors for yield and quality of C. speciosa. However, the underlying mechanisms of root thickening and isoflavonoid biosynthesis have not yet been elucidated. Here, integrated morphological, hormonal and transcriptomic analyses of C. speciosa tuberous roots at four different ages (6, 12, 18, 30 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…We have previously reported that 15 putative structural genes were involved in isoflavonoid biosynthesis, including HI4 ′ OMT , 2 VRs , 3 CHIs , 2 CHSs , 3 HIDs , 2 IFSs , I3 ′ H , and 4CL [ 10 ]. These genes had different expression patterns among the four different developmental stages (6, 12, 24, and 30 MAG).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously reported that 15 putative structural genes were involved in isoflavonoid biosynthesis, including HI4 ′ OMT , 2 VRs , 3 CHIs , 2 CHSs , 3 HIDs , 2 IFSs , I3 ′ H , and 4CL [ 10 ]. These genes had different expression patterns among the four different developmental stages (6, 12, 24, and 30 MAG).…”
Section: Resultsmentioning
confidence: 99%
“…Isoflavonoids are the most important active constituents in C. speciosa [ 25 ]. Isoflavonoids determine the quality of the drugs, and isoflavonoid content varies during the development of tuberous roots [ 10 ]. However, the molecular mechanism of isoflavonoid biosynthesis and accumulation that causes variation in isoflavonoid content remains largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations